Controlling debond on demand performance in adhesive systems using structurally tuned expandable graphite fillers - O Kachouri; J Bardon; D Ruch; A Laachachi (Journal of Advanced Joining Processes)
The emergence of debonding technologies has enabled adhesive systems to better align with the principles of sustainability and the circular economy by addressing the gap between the end-of-life stage of adhesively bonded products and the potential for component reuse. In this context, the present study explores the application of thermally responsive additives to induce controlled debonding in adhesive joints. In our previous investigations, it was shown that integrating various types of flame retardants (intumescent and non-intumescent) significantly reduced the debonding temperature, by altering the thermomechanical properties of the joint at temperatures substantially lower than the degradation onset of the unmodified adhesive system. Expandable graphite (EG), a thermally responsive material, has previously been employed with success for similar purposes. Its incorporation into the adhesive layer, even in trace amounts, results in a very significant expansion upon the application of heat, thereby providing an effective mechanism for disassembling adhesively bonded structural assemblies. The present study builds on this prior research and probes deeper into the manufacturing processes underlying EG. The primary hypothesis explored is whether tailoring these processes can result in modulating the thermal response of adhesives modified by EG, thereby achieving debonding at distinct temperature ranges suitable for a wide spectrum of applications. This study investigates EG-modified adhesives, assessing their mechanical properties, thermomechanical degradation, and microstructural changes using characterization techniques such as pull-off tests, microtomography, TGA, and DMA. Finally, the recycling potential is demonstrated through the successful reuse of debonded substrates after a simple cleaning process.